The effect of venous caffeine on the prevention of apnea of prematurity in the very preterm infants in the neonatal intensive care unit of Shahid Motahhari Hospital, Urmia, during a year - Zahra Fakoor; Ali Aghayar Makooie; Zahra Joudi; Rasool Gharaaghaji Asl (Wolters Kluwer Medknow Publications, 2019)
Due to the importance of prevention of apnea of prematurity in the very preterm infants and the side effects of using methylxanthines in preterm infants, the present study was conducted and aimed at investigating the effects of prophylactic caffeine on the incident of apnea (short-term consequence). This is a clinical-experimental trial, in which the infants were included after receiving written consent from their parents. The infants were randomly divided into two groups, namely, Group A (receive caffeine) and Group B (did not receive caffeine). After sampling of the collected data, the two groups were analyzed using statistical tests using SPSS software 23. Among the 50 infants in the caffeine group and 50 infants in the control group, 1 (2%) and 2 (4%) infants required long-term oxygen, respectively. Three (6%) infants from the caffeine group and 2 (4%) infants from the control group had an intraventricular hemorrhage. Two (4%) infants from the caffeine group and 1 (2%) infant from the control group had a positive patent ductus arteriosus and needed treatment. Among the 50 infants in the caffeine group and 50 infants in the control group, 7 (14%) and 9 (18%) infants had apnea, respectively. According to the Fisher's exact test, there was no significant difference between the incident of apnea in the two groups (P = 0.58). Ten (20%) infants from the caffeine group and 7 (14%) infants from the control group died. The prescription of prophylactic caffeine had no effect on the incident of apnea in the infants. Hence, the use of that should be limited to the preterm infants lower than 1250 g in the prophylactic form.